The Safety Profile of Single Daily Dose of Aminoglycosides in Comparison with Multiple Daily Dose - Amanj A. Baker; Ibrahim A. Majeed; Dawser K. Ismail (College of Pharmacy University of Baghdad, 2017)
To overcome  the  problems  which  associated  with  the standard  multiple  daily  doses (MDD) of aminoglycosides (AGs) like high incidence of toxicity(nephrotoxicity, ototoxicity)(5-25%) and high cost, an alternative approach was developed which was single daily dose (SDD).This new regimen was designed to maximize bacterial killing by optimizing the peak concentration/minimum inhibitory concentration(MIC)ratio and to reduce the potential for toxicity. The study includes 75 patients selected randomly, 50 of them received SDD regimen of age range of 17-79 years and the remaining received MDD regimen of age range of 13-71 years. The study was designed to evaluate the safety of SDD regimen in comparison with MDD regimen. All the patients in SDD group received a constant dose of   5-mg/kg/day of gentamicin and 20mg/kg/day of amikacin with a drug administration interval based on estimated creatinine clearance(CLcr): if â‰¥60 ml//min every 24 hours (q24h), 59- 40 ml/ min every 36hours and 39- 30 ml/min every 48 hours.The calculated dose was diluted with 0.9% normal saline or 5% dextrose to 50-100 ml and given as intravenous infusion over 30-60 minutes. In SDD group , the mean length of therapy was 6.4Â±1.73  days .Gentamicin accounted for 96% of the aminoglycoside use, and the majority(58%) of patients received the drug every 24 hours.The 36- and -48 hours intervals were used for 34 and 8% of the population, respectively.While in MDD group , the mean length of therapy was 5.0Â±0.91 days. Gentamicin accounted for all (100%) of aminoglycoside use, and all of the patients received the drug every 8 hours. No clinically apparent ototoxicity and nephrotoxicity were observed in the patients in the SDD group, in contrast to the patients in MDD group, in whom 4 patients (16%) were developed nephrotoxicity and 1 patient (4%) was developed ototoxicity. The obtained results indicate that SDD regimen was safer through decreasing the incidence of both nephrotoxicity and ototoxicity.For statistical analysis, ANOVA test was used with P<0.01.Each mean was expressed as meanÂ±SEM(Standard Error of Mean). Key words: Aminoglycosides, Single Daily Dose, Nephrotoxicity and Ototoxicity.